Moderasi Islam Era Milenial (Ummatan Wasathan Dalam Moderasi Islam Karya Muchlis Hanafi) - Muhamad Rezi (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2020)
The radical or extreme attitude in religion is not a new phenomenon in Islamic history. Since the earliest period, several religious groups have shown this extreme attitude. Today, the issue of religious-based radicalism is not something that was exhaled just a few days ago. The issue of radicalism has become a global agenda to corner Islam. For some circles in Islam, the issue of radicalism is only propaganda to bring down the dignity and height of Islam. The focus of this paper is not to dismantle and tell a series of acts of terror on the grounds of religion. This article is a reviewer of Islamic Moderation books; Counteracting Religious-Based Radicalism written by Muchlis Hanafi, an expert on the Interpretation of the Indonesian Qur'an. The book with ISBN 978-602-18476-1-9 was published by the Al-Azhar Alumni Association and the Jakarta Qur'an Study Center and first published in 2013 with 295 pages in thickness. Until today, an explanation of the concept of Islamic moderation based on the Koran by promoting the term Wasath as a form of moderate attitude is still very rarely written and presented scientifically like the book of Islamic Moderation; Counteracting Religious-Based Radicalism. The concept of moderation by interpreting the meaning of Wasath is a step forward in proving the relevance of the Qur'an to the times. Both from the aspect of the meaning of language and concrete attitude in everyday life.